Tale of Verlioka in Speech Culture of Belozerye and in Repertoire of Language Personality - E. N. Ilyina (Научный диалог)
The article is devoted to the study of the speech culture of the European North of Russia. Records of the tale of Verlioka, made in Belozerye, from the words of one informant twenty years apart, are being investigated. The conditions of existence of fairy tales, genre affiliation, plot organization, compositional structure, language specifics are considered. The conditions of fairy tales existence, genre affiliation, plot organization, compositional structure, language specifics are considered. It is shown that this character, who is marginal and has very blurred characteristics in the East Slavic territory (O. A. Cherepanova), is the antagonist of the main character, differs in the abnormality / monostructure of the body structure (the presence of only one eye) and cannibalism. It is noted that with all the textual discrepancies, the plot is built around the destruction and its elimination with the help of the main character’s magic helpers (rope / belt, acorn, wand), which in a collision with the antagonist show their miraculous properties. The author concludes that the linguistic features of the fairy tale records are determined by the territorial specificity of the storyteller’s speech and his desire to entertain the interlocutors (in the first version of the record) or to reflect the memories of his family and his native village as fully as possible (in the second version).